La crítica de la novela indigenista colombiana : objeto y problemas (2012)
ABSTRACT: the indigenist novel in Colombia has developed in a similar way of its correlative ones in the Andean countries that typically represent the subgenre in the Latin American literary criticism. However, local criticism related to this kind of novel has shown evident limitations. A review of some representative critical studies shows at least three decisive problems: adherence to the nineteenth-century notion of Indianism, an excessive focus on representative works and the reduction of criticism to comments on specific novels.